Analisis Pendapatan Usaha Tani Agroforestri Di Kawasan Hulu DAS Renggung, Kabupaten Lombok Tengah - Alfian Pujian Hadi; Agus Mulyadi Ashari (Yayasan Tajuk Indonesia, 2024)
Agricultural development in dry land has a big challenge because of the variety and high risks that exist, so that agricultural development in dry land requires special handling and may be more complicated than agriculture in paddy fields. The specific objectives of the study were to determine the types of plants cultivated by dry land farmers, identify the types of risks faced by dry land farmers, determine the perceptions of farmers and informants about each identified risk, The research method used was a descriptive method. The study was conducted in East Lombok Regency, namely in Pringgabaya District. The sample determination was carried out by